High-barrier-property flexible fabric membrane material and preparation method thereof
Through the design of the five-layer composite structure and modified filler, the barrier properties and toughness of the flexible fabric film are improved, and the problems of insufficient barrier properties and easy aging of PVDC films in the prior art are solved, thereby achieving high barrier properties and photo-resistant aging Flexible fabric film material.
Patent Information
- Application Number
- CN202411710181.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing flexible fabric film materials are insufficient in barrier properties, especially when used in VIP board storage, which cannot meet the needs of high airtightness. The PVDC film is temperature sensitive and prone to aging, and the hydrophilic additives will degrade and lose when exposed for a long time. Reduces barrier properties.
High barrier flexibility fabric film materials with five-layer composite structure, including coating layer, PVC layer, adhesive base cloth layer, PVC layer and acrylic layer, improve the barrier stability of PVDC film by making homemade chain transfer agent and modified filler The bonding tightness with the interlayer is used, and modified polymethyl methacrylate and calcium titanium dioxide stearate are used as fillers to optimize the molecular structure of the PVDC film and the dynamic release of the interlayer interface, enhancing the film's photoaging and barrier properties.
A flexible fabric film with high barrier properties and good toughness is achieved, which solves the problems of temperature sensitivity of PVDC film and easy degradation of hydrophilic additives, improves the barrier stability and interlayer binding force of the film, and enhances the photo-resistant and aging properties of the film. and processing performance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy, and in particular relates to a high-barrier flexible fabric membrane material and a preparation method thereof. Background Art
[0002] Flexible fabric membrane is a composite material composed of a fiber fabric base and an outer coating. The fiber fabric base is generally made of polyester fiber and glass fiber, which mainly bears and transfers loads. Polyester fiber has good deformation ability and high strength, but is easy to age; while glass fiber has small deformation, high strength, and strong anti-aging ability, but is relatively brittle. The outer coating of the membrane mainly seals and protects the base. In addition, it is also necessary to ensure the waterproof, fire-resistant, durable, light-transmitting and self-cleaning properties of the material.
[0003] Patent CN104108211B discloses a lightweight, high-strength inflatable membrane structural material and its preparation. The inflatable membrane material has the performance characteristics of light weight and high strength, good air and water barrier, weather resistance and self-cleaning properties. From the outside to the inside, it is respectively a weather-resistant layer, a welding barrier layer, a load-bearing layer, a welding barrier layer and a weather-resistant layer. Although the mechanical properties of this inflatable membrane material are excellent, its barrier properties still have room for further improvement. CN110329647A provides a highly airtight barrier film and a packaging bag with the barrier film. The barrier film is composed of an EVA layer, a PE layer and a VMPA layer that are arranged in sequence. It has excellent barrier properties and is convenient for the storage of VIP sheets. However, the water vapor permeability in the performance test (all greater than 10mg / m 2 ) It can be seen that the barrier film can meet the airtightness requirements of packaging bags, but when applied to flexible fabric film materials, its barrier properties need to be further improved. Summary of the invention
[0004] In order to overcome the above-mentioned deficiencies of the prior art, the present invention obtains a flexible fabric membrane material with high barrier properties by closely combining multiple layers of materials.
[0005] To achieve the above purpose, the technical solution adopted by the present invention is: The first aspect of the present invention provides a high-barrier flexible fabric membrane material, which comprises a five-layer composite structure from top to bottom, namely: a coating layer, a PVC layer, an adhesive base fabric layer, a PVC layer and an acrylic layer; the coating layer is a composite PVDC film; based on 100wt%, the raw materials of the PVC layer comprise 48-50wt% PVC resin, 24-26wt% diisononyl phthalate, 1-2wt% triphenyl phosphate, 3-5wt% diisooctyl adipate, 0.5-1wt% calcium zinc stabilizer, 0.2-0.3wt% polyethylene wax, 5-6wt% aluminum hydroxide, 5-6wt% calcium carbonate and 8-10wt% titanium dioxide.
[0006] In some embodiments, the thickness of the coating layer is 70-100 μm, the thickness of the PVC layer is 200-250 μm, the thickness of the adhesive base fabric layer is 480-520 μm, and the thickness of the acrylic layer is 65-85 μm.
[0007] In some embodiments, the steps of preparing the coating layer are as follows: S1, at -2~2 o C and inert gas protection, stirring sodium hydride, 4-methylaminopyridine, and tetrahydrofuran for 1.5-2.5 h, adding carbon disulfide dropwise, stirring at room temperature for 10-16 h after the addition is complete, then adding 4-vinylbenzyl chloride, continuing to stir for 2-4 h, extracting after the stirring is completed, washing the organic phase, drying, rotary evaporating, and chromatographically purifying to obtain a chain transfer agent; S2, methyl methacrylate, N-hydroxyethyl acrylamide, the chain transfer agent obtained in step S1 and N-methyl pyrrolidone are stirred at room temperature until dissolved, and then azobisisobutyronitrile is added, and the mixture is heated to 65-75 ℃ under an inert gas atmosphere. o C for 45-50 hours, then put into ice ether for precipitation, filter, and vacuum dry at room temperature for 42-50 hours to obtain an amphiphilic additive; S3, PVDC, the amphiphilic additive obtained in step S2 and DMF-THF mixed solvent were mixed at 50-70 o C for 5-7h, then add the modified filler and stir evenly, pour into the mold and heat at 140-180 o C for curing for 50-100 min, and then demoulding to obtain the coating layer.
[0008] PVDC has high barrier properties and is suitable as the outer film layer of flexible fabric membranes. However, it is sensitive to temperature. o C rises to 60 o C, its permeability coefficient increases by about 100 times. The applicant improves the barrier stability of PVDC by adding hydrophilic polymethyl methacrylate. However, when the hydrophilic polymethyl methacrylate is exposed to the natural environment for a long time, it will gradually degrade and be lost from the membrane. This may be caused by the insufficient chain entanglement between it and PVDC.
[0009] Due to the complex production process of PVDC, the modification of its molecular structure can easily cause the degradation of its own performance. For this reason, the applicant chose to modify polymethyl methacrylate to obtain an amphiphilic additive. On the one hand, the hydrophilic functional groups are enriched on the surface of the polyvinylidene fluoride membrane due to hydration; on the other hand, there is a hydrophobic effect and chain entanglement between the hydrophobic chain segments and the PVDC matrix chain segments, which anchors the additives and makes the chains tightly entangled. The two aspects work together to make the PVDC membrane have excellent barrier stability. However, the applicant also found that the average pore size and porosity of the PVDC membrane increased, which led to a decrease in the barrier properties of the flexible fabric membrane material. The possible reason is that the introduction of amphiphilic additives makes the system thermodynamically unstable, which will accelerate the exchange rate of solvent and air, resulting in an increase in the membrane phase separation rate, thereby promoting the formation and development of membrane pores.
[0010] To this end, the applicant reduced the degree of polymerization of the branched chain segments in the additive by making a self-made chain transfer agent, thereby reducing the membrane phase separation rate and the formation of pores. In addition, the applicant made a specific selection of the raw materials of the additive to achieve a better combination with the chain transfer agent, thereby promoting the hydration of the hydroxyl groups and amide bonds in the formed additive molecules, avoiding the reduction of membrane thickness and enlargement of pores caused by the shrinkage of the hydrophilic functional groups on the PVDC matrix and surface due to dehydration during the drying process.
[0011] In some embodiments, in step S1, the mass ratio of 4-methylaminopyridine, carbon disulfide and 4-vinylbenzyl chloride is (0.75-0.83):(1.26-1.30):1.
[0012] In some embodiments, the mass ratio of methyl methacrylate, N-hydroxyethyl acrylamide and chain transfer agent in step S2 is 1:(1.0-1.3):(0.14-0.16).
[0013] In some embodiments, the mass ratio of PVDC, reactant and modified filler in step S3 is 1:(0.120-0.138):(0.28-0.32).
[0014] In some embodiments, the preparation steps of the modified filler in step S3 are as follows: titanium dioxide and calcium stearate are placed in an EDTA solution and stirred for 10-14 hours, and then filtered, washed, and dried to obtain the modified filler.
[0015] In some embodiments, the concentration of the EDTA solution is 0.08-0.12 mol / L.
[0016] In some embodiments, the mass ratio of titanium dioxide to calcium stearate is (120-140):1.
[0017] In the preparation of the film layer, the applicant selected titanium dioxide and calcium stearate as fillers, among which titanium dioxide has a certain ultraviolet absorption ability, which can improve the light aging resistance of the film layer, and the dispersibility is enhanced by modifying the two fillers. In addition, the applicant accidentally discovered that the modified filler can enhance the tightness of the bonding between the film layer and the PVC layer. The possible reason is that the EDTA contained in the modified filler can be dynamically released at the film layer / PVC slurry interface, and the calcium ions and zinc ions in the calcium zinc stabilizer in the PVC are interfacially chelated, which strengthens the bonding of the two layers to a certain extent and improves the peeling strength.
[0018] In some embodiments, the mass ratio of titanium dioxide to calcium stearate is (128-132):1.
[0019] In some embodiments, the preparation steps of the adhesive base fabric layer are as follows: the base fabric is impregnated with a polyurethane-tetrahydrofuran solution, and the amount of glue applied is controlled to be 100-150 g / m 2 After gluing, attach aluminum foil on both sides, dry at 100-110℃ for 30-50min, and continue to immerse in polyurethane-tetrahydrofuran solution after cooling to room temperature. The amount of glue is controlled at 200-350g / m 2 After gluing, the adhesive base fabric layer is obtained by drying at 100-110°C for 40-60 minutes.
[0020] Preferably, the base fabric is woven from polyester fibers.
[0021] Preferably, the polyurethane is thermoplastic polyurethane.
[0022] A second aspect of the present invention provides a method for preparing a high barrier flexible fabric membrane material, comprising the following steps: (1) Stirring PVC resin, diisononyl phthalate and triphenyl phosphate for 50-70 minutes, then adding diisooctyl adipate, calcium zinc stabilizer, polyethylene wax, aluminum hydroxide, calcium carbonate and titanium dioxide, and stirring at a speed of 800-1200 rpm to obtain PVC slurry; (2) casting the PVC slurry on the film layer, leaving it to stand for 10-20 minutes and then drying it at 110-130° C. for 10-20 minutes to form a PVC layer on the film layer, thereby obtaining a composite layer 1; (3) casting the PVC slurry on the acrylic layer, drying at 110-130° C. for 10-20 min, forming a PVC layer on the acrylic layer, and obtaining a composite layer 2; (4) placing an adhesive base fabric layer between the PVC layers of the combined layer 1 and the combined layer 2, and hot pressing and molding the layer at 140-150° C. and 6-8 MPa to obtain the high barrier flexible fabric membrane.
[0023] In some embodiments, the preparation step of the acrylic layer is as follows: based on 100wt%, 70-78wt% of polymethyl methacrylate, 10-20wt% of PVC resin, 7-9wt% of diisononyl phthalate, 1.0-1.5wt% of calcium zinc stabilizer, 0.2-0.3wt% of polyethylene wax, 1-2wt% of titanium dioxide, 0.2-0.3wt% of β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol and 0.1-0.2wt% of tris(2,4-di-tert-butyl)phenyl phosphite are added at 140-150°C. o C, and then cooled at room temperature for 10-14 hours to obtain the acrylic layer.
[0024] The applicant has made the best use of the modification of the coating layer by specifically selecting the preparation method, and has achieved close bonding between the layers, so that the flexible fabric membrane material not only has excellent barrier properties, but also has good toughness and is easy to process.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention provides a flexible fabric membrane material with good barrier properties and good toughness.
[0027] 2. The present invention improves the barrier stability of the PVDC layer by using a self-made amphiphilic additive, and solves the problem that the additive will gradually degrade and be lost from the film after being exposed to the natural environment for a long time by modifying the additive.
[0028] 3. The present invention reduces the degree of polymerization of the branched chain segments in the amphiphilic additive by making a self-made chain transfer agent, thereby solving the problem of increased average pore size and porosity caused by the amphiphilic additive.
[0029] 4. The present invention improves the dispersibility of the filler and the light aging resistance of the coating layer by performing specific modification on the filler, and at the same time strengthens the bonding tightness between the coating layer and the PVC layer. DETAILED DESCRIPTION
[0030] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following examples and comparative examples are examples of the present invention and are only used to illustrate the present invention, but not to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0031] It is worth noting that the raw materials used in the following preparation examples and embodiments are all from any commercially available manufacturers unless otherwise specified.
[0032] Preparation Example 1 The preparation steps of modified filler-A are as follows: 130g titanium dioxide and 1g calcium stearate were placed in 700mL 0.1mol / L EDTA solution and stirred for 12h, then filtered, washed with deionized water, and 100 o C and dried for 6 h to obtain modified filler-A.
[0033] Preparation Example 2 The preparation steps of modified filler-B are as follows: The difference between this preparation example and preparation example 1 is that the amount of titanium dioxide used is 115 g.
[0034] Preparation Example 3 The preparation steps of modified filler-C are as follows: The difference between this preparation example and preparation example 1 is that the amount of titanium dioxide used is 145 g.
[0035] Preparation Example 4 The preparation steps of coating layer-A are as follows: S1, at 0 o C and nitrogen protection, 2.9g sodium hydride, 8.7g 4-methylaminopyridine, 400mL tetrahydrofuran were stirred for 2h, 14.1g carbon disulfide was added dropwise, and stirred at room temperature for 13h after the addition was completed, and then 11g 4-vinylbenzyl chloride was added, and stirring was continued for 3h. After the stirring was completed, 100mL methanol and 60mL saturated sodium bicarbonate solution were added and mixed, and then extracted with 500mL dichloromethane. After the extraction was completed, the organic phase was washed with saturated sodium bicarbonate solution and deionized water for 3 times respectively, and the residual water was dried with magnesium sulfate, and then dichloromethane was removed by rotary evaporation, followed by silica gel chromatography purification to obtain a chain transfer agent; S2, 30g methyl methacrylate, 34.5g N-hydroxyethyl acrylamide, 4.4g chain transfer agent obtained in step S1 and 280g N-methyl pyrrolidone were stirred at room temperature until dissolved, and then 0.33g azobisisobutyronitrile was added, and the mixture was stirred at room temperature under nitrogen protection and 70 o C for 48 h, then put into 1000 mL of ice ether for precipitation, filter, and vacuum dry at room temperature for 48 h to obtain an amphiphilic additive; S3, PVDC, 12.9 g of the reactant obtained in step S2 and 800 mL of a mixed solvent of DMF and THF in a volume ratio of 1:1 were added at 60 o C for 6 h, add 30 g of modified filler-A, stir evenly, and heat in a mold at 180 o C for 90 min, and then demoulding to obtain the coating layer-A.
[0036] Preparation Example 5 The preparation steps of coating layer-B are as follows: The difference between this preparation example and preparation example 1 is that: S3, 100g PVDC, 12.9g of the reactant obtained in step S2 and 800mL of a mixed solvent of DMF and THF in a volume ratio of 1:1 were added at 60 o C for 6 h, add 29.7 g titanium dioxide and 0.3 g calcium stearate and mix well. o C for 90 min, and then demoulding to obtain the coating layer-B.
[0037] Preparation Example 6 The preparation steps of coating layer-C are as follows: 100 g PVDC, 12.9 g polymethyl methacrylate and 800 mL DMF and THF (volume ratio 1:1) were mixed at 60 o C for 6 h, add 30 g of the modified filler-A obtained in Preparation Example 1 and stir evenly, and heat in a mold at 180 o C for 90 min, and then demolding to obtain the coating layer-C.
[0038] Preparation Example 7 The preparation steps of coating layer-D are as follows: The difference between this preparation example and preparation example 1 is that in step S3, the modified filler-A is replaced by an equal amount of modified filler-B.
[0039] Preparation Example 8 The preparation steps of coating layer-E are as follows: The difference between this preparation example and preparation example 1 is that in step S3, the modified filler-A is replaced by an equal amount of modified filler-C.
[0040] Preparation Example 9 The preparation steps of coating layer-F are as follows: The difference between this preparation example and preparation example 1 is that the mass of 4-vinylbenzyl chloride in step S1 is 8 g.
[0041] Preparation Example 10 The preparation steps of coating layer-G are as follows: The difference between this preparation example and preparation example 1 is that the mass of 4-vinylbenzyl chloride in step S1 is 14 g.
[0042] Preparation Example 11 The steps for preparing the acrylic layer are as follows: Based on 100wt%, 74wt% polymethyl methacrylate, 15wt% PVC resin, 7.85wt% diisononyl phthalate, 1.2wt% calcium zinc stabilizer, 0.25wt% polyethylene wax, 1.2wt% titanium dioxide, 0.25wt% β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl ester and 0.25wt% tri(2,4-di-tert-butyl)phenyl phosphite were added at 165 °C. o C and then cooled at room temperature for 12 h to obtain the acrylic layer.
[0043] Preparation Example 12 The steps for preparing the bonding base fabric layer are as follows: The PET cloth was impregnated with a thermoplastic polyurethane-tetrahydrofuran solution with a mass ratio of 1:1.5, and the glue amount was controlled at 125g / m 2 After gluing, aluminum foil was attached to both sides, and the surface was dried at 105°C for 40 minutes. After cooling to room temperature, the surface was immersed in polyurethane-tetrahydrofuran solution. The amount of glue was controlled at 300g / m 2 After gluing, the fabric is dried at 105°C for 50 minutes to obtain a bonding base fabric layer.
[0044] Example 1 A high-barrier flexible fabric membrane material comprises a five-layer composite structure from top to bottom, namely: a coating layer-A, a PVC layer, an adhesive base fabric layer, a PVC layer and an acrylic layer; The method for preparing the high barrier flexible fabric membrane in this embodiment comprises the following steps: (1) Based on 100wt%, 49wt% of PVC resin, 25wt% of diisononyl phthalate and 1.5wt% of triphenyl phosphate were stirred for 60min, and then 3wt% of diisooctyl adipate, 0.75wt% of calcium zinc stabilizer, 0.25wt% of polyethylene wax, 5.5wt% of aluminum hydroxide, 5.5wt% of calcium carbonate and 10wt% of titanium dioxide were added, and the mixture was stirred at a speed of 1000rpm to obtain a PVC slurry; (2) casting the PVC slurry on the coating layer-A with a thickness of 85 μm, standing for 15 minutes and then drying at 120° C. for 15 minutes to form a PVC layer with a thickness of 230 μm on the coating layer-A, thereby obtaining a composite layer 1; (3) casting the PVC slurry on an acrylic layer with a thickness of 75 μm, drying at 120° C. for 15 min, and forming a PVC layer with a thickness of 230 μm on the acrylic layer to obtain a composite layer 2; (4) A 500 μm thick adhesive base fabric layer is placed between the PVC layers of the combination layer 1 and the combination layer 2, and hot pressing is performed at 145° C. and 7 MPa for 4 min to obtain a high barrier flexible fabric membrane material.
[0045] Example 2 A high-barrier flexible fabric membrane material comprises a five-layer composite structure from top to bottom, namely: a coating layer-A, a PVC layer, an adhesive base fabric layer, a PVC layer and an acrylic layer; The method for preparing the high barrier flexible fabric membrane in this embodiment comprises the following steps: (1) Based on 100wt%, 48wt% of PVC resin, 24wt% of diisononyl phthalate and 1wt% of triphenyl phosphate were stirred for 50min, and then 5wt% of diisooctyl adipate, 1wt% of calcium zinc stabilizer, 0.3wt% of polyethylene wax, 6wt% of aluminum hydroxide, 6wt% of calcium carbonate and 8.7wt% of titanium dioxide were added, and the mixture was stirred at a speed of 800rpm to obtain a PVC slurry; (2) casting the PVC slurry on the coating layer-A with a thickness of 85 μm, leaving it to stand for 10 min and then drying it at 110° C. for 20 min, thereby forming a PVC layer with a thickness of 230 μm on the coating layer-A, thereby obtaining a composite layer 1; (3) casting the PVC slurry on an acrylic layer with a thickness of 75 μm, drying at 110° C. for 20 min, and forming a PVC layer with a thickness of 230 μm on the acrylic layer to obtain a composite layer 2; (4) A 500 μm thick adhesive base fabric layer is placed between the PVC layers of the combination layer 1 and the combination layer 2, and hot pressing is performed at 140° C. and 8 MPa for 5 min to obtain a high barrier flexible fabric membrane material.
[0046] Example 3 A high-barrier flexible fabric membrane material comprises a five-layer composite structure from top to bottom, namely: a coating layer-A, a PVC layer, an adhesive base fabric layer, a PVC layer and an acrylic layer; The method for preparing the high barrier flexible fabric membrane in this embodiment comprises the following steps: (1) Based on 100wt%, 50wt% of PVC resin, 26wt% of diisononyl phthalate and 2wt% of triphenyl phosphate were stirred for 70min, and then 3.3wt% of diisooctyl adipate, 0.5wt% of calcium zinc stabilizer, 0.2wt% of polyethylene wax, 5wt% of aluminum hydroxide, 5wt% of calcium carbonate and 8wt% of titanium dioxide were added, and the mixture was stirred at a speed of 1000rpm to obtain a PVC slurry; (2) casting the PVC slurry on the coating layer-A with a thickness of 85 μm, standing for 20 minutes and then drying at 130° C. for 10 minutes to form a PVC layer with a thickness of 230 μm on the coating layer-A, thereby obtaining a composite layer 1; (3) casting the PVC slurry on an acrylic layer with a thickness of 75 μm, drying at 130° C. for 10 min, and forming a PVC layer with a thickness of 230 μm on the acrylic layer to obtain a composite layer 2; (4) A 500 μm thick adhesive base fabric layer is placed between the PVC layers of the combination layer 1 and the combination layer 2, and hot pressing is performed at 150° C. and 6 MPa for 3 min to obtain a high barrier flexible fabric membrane material.
[0047] Example 4 This embodiment provides a high-barrier flexible fabric membrane material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the coating layer-A is replaced by the coating layer-B.
[0048] Example 5 This embodiment provides a high barrier flexible fabric membrane material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the coating layer-A is replaced by the coating layer-C.
[0049] Example 6 This embodiment provides a high barrier flexible fabric membrane material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the coating layer-A is replaced by the coating layer-D.
[0050] Example 7 This embodiment provides a high-barrier flexible fabric membrane material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the coating layer-A is replaced by the coating layer-E.
[0051] Example 8 This embodiment provides a high barrier flexible fabric membrane material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the coating layer-A is replaced by the coating layer-F.
[0052] Example 9 This embodiment provides a high barrier flexible fabric membrane material and a preparation method thereof. The specific implementation method is the same as that of Embodiment 1, except that the coating layer-A is replaced by the coating layer-G.
[0053] Example 10 This embodiment provides a high barrier flexible fabric membrane material and a preparation method thereof. The difference is that the preparation method of the high barrier flexible fabric membrane material in this embodiment comprises the following steps: (1) Based on 100wt%, 49wt% PVC resin, 25wt% diisononyl phthalate and 1.5wt% triphenyl phosphate were stirred for 60min, followed by the addition of 4wt% diisooctyl adipate, 0.75wt% calcium zinc stabilizer, 0.25wt% polyethylene wax, 5.5wt% aluminum hydroxide, 5.5wt% calcium carbonate and 9wt% titanium dioxide, and the mixture was stirred at 1000rpm and dried at 120°C for 15min to obtain a PVC layer with a thickness of 230μm; (2) A PVC layer, a 500 μm thick adhesive base fabric layer, a PVC layer, and a 85 μm thick coating layer-A are placed in sequence on an acrylic layer with a thickness of 75 μm, and hot pressed for 4 min at 145°C and 7 MPa to obtain a high barrier flexible fabric membrane material.
[0054] Performance Testing The flexible fabric membranes prepared in the above examples were tested for the following properties: 1. Barrier test see Table 1; 2. The bonding strength test between film layers is shown in Table 1.
[0055] Table 1
[0056] From the data in Table 1, it can be seen that the barrier properties of the flexible fabric membranes of Examples 1-3 are excellent, and the membrane layers are tightly bonded; from Examples 1 and 4 and Examples 6-7, it can be seen that the modified filler in the film layer can strengthen the bond between the film layer and the PVC layer to a certain extent; from Examples 1 and 8-9, it can be seen that a specific chain transfer agent can strengthen the barrier properties of the film layer. From Examples 1 and 10, it can be seen that selecting a suitable flexible fabric membrane preparation process according to the preparation characteristics of different film layers can better give play to the advantages of each film layer.
[0057] The embodiments described above do not impose any form of limitation on the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A high barrier flexible fabric membrane material, characterized in that: The flexible fabric membrane material comprises a five-layer composite structure from top to bottom, namely: a coating layer, a PVC layer, an adhesive base fabric layer, a PVC layer and an acrylic layer; The coating layer is a composite PVDC film; Based on 100wt%, the PVC layer raw material comprises 48-50wt% PVC resin, 24-26wt% diisononyl phthalate, 1-2wt% triphenyl phosphate, 3-5wt% diisooctyl adipate, 0.5-1wt% calcium zinc stabilizer, 0.2-0.3wt% polyethylene wax, 5-6wt% aluminum hydroxide, 5-6wt% calcium carbonate and 8-10wt% titanium dioxide.
2. The high barrier flexible fabric membrane material according to claim 1, characterized in that: The thickness of the coating layer is 70-100 μm, the thickness of the PVC layer is 200-250 μm, the thickness of the bonding base fabric layer is 480-520 μm, and the thickness of the acrylic layer is 65-85 μm.
3. The high barrier flexible fabric membrane material according to claim 1, characterized in that: The steps of preparing the coating layer are as follows: S1, at -2~2 o C and inert gas protection, stirring sodium hydride, 4-methylaminopyridine, and tetrahydrofuran for 1.5-2.5 h, adding carbon disulfide dropwise, stirring at room temperature for 10-16 h after the addition is complete, then adding 4-vinylbenzyl chloride, continuing to stir for 2-4 h, extracting after the stirring is completed, washing the organic phase, drying, rotary evaporating, and chromatographically purifying to obtain a chain transfer agent; S2, methyl methacrylate, N-hydroxyethyl acrylamide, the chain transfer agent obtained in step S1 and N-methyl pyrrolidone are stirred at room temperature until dissolved, and then azobisisobutyronitrile is added, and the mixture is heated to 65-75 ℃ under an inert gas atmosphere. o C for 45-50 hours, then put into ice ether for precipitation, filter, and vacuum dry at room temperature for 42-50 hours to obtain an amphiphilic additive; S3, PVDC, the reactant obtained in step S2 and DMF-THF mixed solvent were heated at 50-70 o C for 5-7h, then add the modified filler and stir evenly, pour into the mold and heat at 140-180 o C for curing for 50-100 min, and then demoulding to obtain the coating layer.
4. The high barrier flexible fabric membrane material according to claim 3, characterized in that: In the step S1, the mass ratio of 4-methylaminopyridine, carbon disulfide and 4-vinylbenzyl chloride is (0.75-0.83):(1.26-1.30):
1.
5. The high barrier flexible fabric membrane material according to claim 3, characterized in that: In the step S2, the mass ratio of methyl methacrylate, N-hydroxyethyl acrylamide and chain transfer agent is 1:(1.0-1.3):(0.14-0.16).
6. The high barrier flexible fabric membrane material according to claim 3, characterized in that: In the step S3, the mass ratio of PVDC, reactant and modified filler is 1:(0.120-0.138):(0.28-0.32).
7. The high barrier flexible fabric membrane material according to claim 3, characterized in that: The preparation steps of the modified filler in step S3 are as follows: titanium dioxide and calcium stearate are placed in an EDTA solution and stirred for 10-14 hours, and then filtered, washed, and dried to obtain the modified filler.
8. The high barrier flexible fabric membrane material according to claim 7, characterized in that: The mass ratio of the titanium dioxide to calcium stearate is (120-140):
1.
9. The high barrier flexible fabric membrane material according to claim 1, characterized in that: The preparation steps of the adhesive base fabric layer are as follows: the base fabric is impregnated with a polyurethane-tetrahydrofuran solution, and the amount of glue applied is controlled at 100-150 g / m 2 After gluing, attach aluminum foil on both sides, dry at 100-110℃ for 30-50min, and continue to immerse in polyurethane-tetrahydrofuran solution after cooling to room temperature. The amount of glue is controlled at 200-350g / m 2 After gluing, the adhesive base fabric layer is obtained by drying at 100-110°C for 40-60 minutes.
10. A method for preparing a high barrier flexible fabric membrane according to any one of claims 1 to 9, characterized in that: The preparation steps are as follows: (1) Stirring PVC resin, diisononyl phthalate and triphenyl phosphate for 50-70 minutes, then adding diisooctyl adipate, calcium zinc stabilizer, polyethylene wax, aluminum hydroxide, calcium carbonate and titanium dioxide, and stirring at a speed of 800-1200 rpm to obtain PVC slurry; (2) casting the PVC slurry on the film layer, leaving it to stand for 10-20 minutes and then drying it at 110-130° C. for 10-20 minutes to form a PVC layer on the film layer, thereby obtaining a composite layer 1; (3) casting the PVC slurry on the acrylic layer, drying at 110-130° C. for 10-20 min, forming a PVC layer on the acrylic layer, and obtaining a composite layer 2; (4) placing an adhesive base fabric layer between the PVC layers of the combined layer 1 and the combined layer 2, and hot pressing and molding the layer at 140-150° C. and 6-8 MPa to obtain the high barrier flexible fabric membrane.